Exchange of Publications and Services as a Source for Collection Development - A Case Study - Arora, Pavan; Ragavan, M. C. (Journal of Information and Knowledge, 1982)
The CRRI has developed a system of exchange of publications as a mode for collection development. In addition to exchange of publications, the extension of certain services also contribute towards enriching the collection. CRRI acting as an input centre to international databases and as correspondent for international organisations is able to acquire valuable research publications. A cost benefit study of the CRRI's exchange of publications and services programme is attempted.